Desempenho e Digestibilidade in vivo de Cordeiros Alimentados com Dietas Contendo Canola em Grão Integral em Diferentes Formas - Bett, Vanderlei [UNESP]; Dos Santos, Geraldo Tadeu; Aroeira, Luiz Januário Magalhães; Petit, Hèléne V.; Dias, Priscila Gongora; Leggi, Thelma Cristina Dos Santos Soares; Peron, Karla de Faria; Zeoula, Lúcia Maria (FapUNIFESP (SciELO), 1999)
The performance and digestibility of nutrients of lambs fed concentrates formulated with soybean meal (SM) and whole canola grain (WC), cracked canola grain (CC) or pelleted canola (PC) and oat hay, fed in a 30:70 (forage to concentrate ratio, %DM) were evaluated. Twenty-eight male lambs with initial age from 60 to 90 days and 17 kg LW were allotted to a completely randomized design. The intakes (g/d) of DM, CP, ADF, NDFandGE (Mcal/d), the average daily gain and feed: gain ratio, were similar. There were no differences for apparent digestibilities of MS, PB and GE, except for the NDF digestibility (46.84, 60.11, 50.10, and 38.88%) and ADF (45.84, 54.19, 46.57, and 29.59%) for SM, WC, CC and PC, respectively. There was lower nitrogen retention for CP (3.0 g/d) comparing to the other diets (between 5.0 and 7.3 g/d). The treatments did not differ on the propionate concentration, but reduced the concentrations of butyrate (7.08, 4.87, 4.08, and 4.29 μM/mL of ruminal fluid) and ammonia-N (12.17, 8.69, 8.40, and 7.66 mg/100 mL of ruminal fluid). The use of canola, in the different forms, did not affect the intake and digestion, providing similar performance among the treatments.
Performance and Digestibility in vivo of Lambs Fed Diets with Whole Canola Grain in Different Forms
Keywords: Ammonia-N; Canola seed; Digestibility; Lambs; Rumen pH; VFA; Brassica napus var. napus; Glycine max; Ovis aries; Sinapis arvensis